Determination of the intensity of a power jump session by means of heart rate monitoring - Talita Grossl; Luiz Guilherme Antonacci Guglielmo; Lorival José Carminatti; Juliano Fernandes da Silva (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n2p129 A Power Jump (PJ) session is considered to be a safe and easy class that also involves intermittent exercises that prolong the time to exhaustion. However, there is not enough information about this subject in the literature. The purpose of this study was to determine the intensity of a PJ session by means of heart rate (HR) monitoring. Eleven physically active females participated in the study (age: 21.7 ± 1.9 years; body mass: 59.3 ± 4.8 kg; height: 162.6 ± 5.6 cm; percentage body fat: 22.6 ± 3.2 %). Participants were asked to perform an incremental test (IT), in order to obtain values for oxygen uptake (VO2), maximal heart rate (HRmax), heart rate deflection point (HRDP) and energy expenditure (EE). The HR of the subjects was monitored during a special type of Power Jump session called "mix nine" on two different occasions. According to the HRDP values, physiological domains could be divided into three exercise intensity classes: moderate, heavy and severe. Descriptive statistics were adopted (mean ± SD). Student's t test was used to compare HR and EE between PJ1 and PJ2. For comparisons between domains, two-way ANOVA and the Scheffé test were used. The level of significance was set at p<0.05. Mean HRmax obtained during the IT was 195±10bpm. The velocities, HR and %HRmax corresponding to HRDP and 80% of HRDP were 10.1±0.95km.h-1, 178±7bpm and 91.7±4.0%; and 8.1±0.76km.h-1, 143±5bpm and 73.4±3.2%, respectively. Values for HRmean and EE were significantly different when PJ1 (161±11bpm, 386±58.2kcal) and PJ2 (156±10bpm, 355.1±53.8kcal) were compared. The times spent in each exercise intensity domain were: heavy 51±14.5%; severe 27±19.7% and moderate 23±8.7%. These results show that the subjects spent most of the time in the heavy exercise domain which, in turn, appears to be the most indicated for improving aerobic capacity.